2021
DOI: 10.3390/galaxies9030060
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin and Evolution of the Intra-Cluster Light: A Brief Review of the Most Recent Developments

Abstract: Not all the light in galaxy groups and clusters comes from stars that are bound to galaxies. A significant fraction of it constitutes the so-called intracluster or diffuse light (ICL), a low surface brightness component of groups/clusters generally found in the surroundings of the brightest cluster galaxies and intermediate/massive satellites. In this review, I will describe the mechanisms responsible for its formation and evolution, considering the large contribution given to the topic in the last decades by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 136 publications
1
36
0
Order By: Relevance
“…For further details about the profiles, and in particular about the free parameter γ, we refer the reader to Contini & Gu (2020, 2021. We just stress here that, being the following analysis focused at the present time, the value of γ used is 3, which means that the ICL is more concentrated than the DM halo in which it resides.…”
Section: Bcg and Icl Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…For further details about the profiles, and in particular about the free parameter γ, we refer the reader to Contini & Gu (2020, 2021. We just stress here that, being the following analysis focused at the present time, the value of γ used is 3, which means that the ICL is more concentrated than the DM halo in which it resides.…”
Section: Bcg and Icl Profilesmentioning
confidence: 99%
“…Generally known as Intra-Cluster Light (ICL), or Diffuse Stellar Component (DSC), it is made of stars that are not gravitationally bound to any cluster galaxy and feels only the potential well of the dark matter (DM) halo. Although the ICL is spread along the whole group/cluster, most of it is usually associated with the Brightest Cluster Galaxy (BCG), which is the galaxy residing at the centre of the DM halo, but considerable amounts of ICL are predicted (e.g., Contini et al 2014Contini et al , 2018 and found (e.g., Gonzalez et al 2013;Presotto et al 2014) to be concentrated around intermediate and massive galaxies (for an introductory review on the ICL see Montes 2019or Contini 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…almost exclusively composed of old, red, low-mass stars. Whereas these cluster galaxies often exhibit super-solar abundance ratios of their stars 16 (Fig. 6), their stellar populations have mostly low masses (< 8 M ) and long lifetimes, implying that they should in principle explode as SNIa and inject large amounts of Fe-peak elements in the ICM over cosmic time.…”
Section: Chemical Composition Of the Icmmentioning
confidence: 99%
“…amount, color) are fundamental to set constrains for numerical simulations [32,33,11,15,34], and to reduce the discrepancy between observations and cosmological simulations on the baryon component of the universe [35]. An aspect that is still much debated in literature, both from a theoretical and observational side, regards how the ICL fraction relates to the virial mass (M vir ) of the host environment [36,37]. From a theoretical point of view, Lin and Mohr [38], Murante et al [25], Purcell et al [26] and Henden et al [39] found a slight increase in the ICL fraction in systems with higher M vir .…”
Section: Introductionmentioning
confidence: 99%